1972
DOI: 10.1002/cne.901440302
|View full text |Cite
|
Sign up to set email alerts
|

A study of the organization of apical dendrites in the somatic sensory cortex of the rat

Abstract: In the parietal cortex of the rat, sections cut tangentially show that profiles of medium and large apical dendrites are grouped into clusters. The number of apical dendrites in each cluster is variable and the usual separation between individual clusters is about 50 p. Despite these variations the pattern does not appear to be randgm. Reconstructions from one micron serial sections show that neurons giving rise to the ascending dendrites forming clusters are located at different levels in layer V. The cell bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(70 citation statements)
references
References 11 publications
6
64
0
Order By: Relevance
“…Apical dendrites of layer V pyramidal neurons tend to form bundles (Peters and Walsh, 1972;Sethares, 1991, 1996;Jones, 2000;Rockland and Ichinohe, 2004;DeFelipe, 2005;Innocenti and Vercelli, 2010). However, in Crym-BAC-EGFP mice, many EGFP(ϩ) cells did not appear to form distinct dendritic bundles ( Fig.…”
Section: Relationship To Previously Characterized Neocortical Structuresmentioning
confidence: 95%
“…Apical dendrites of layer V pyramidal neurons tend to form bundles (Peters and Walsh, 1972;Sethares, 1991, 1996;Jones, 2000;Rockland and Ichinohe, 2004;DeFelipe, 2005;Innocenti and Vercelli, 2010). However, in Crym-BAC-EGFP mice, many EGFP(ϩ) cells did not appear to form distinct dendritic bundles ( Fig.…”
Section: Relationship To Previously Characterized Neocortical Structuresmentioning
confidence: 95%
“…At the level of layer 2/3, the apical dendrites begin to branch into terminal tufts, causing bundles to be less spatially confined. It is also evident that the layer 5B pyramidal cell bodies are located vertically below their apical dendrite and that apical dendrites in a given bundle originate from cell somata arranged in clusters (Peters and Walsh, 1972). Each bundle is made up of 5-10 main apical dendrites and their associated somata, with distances of 20 -40 m between the bundle centers.…”
Section: Characterization Of Bundles Formed By Apical Dendrites Of Lamentioning
confidence: 99%
“…It has been suggested that pyramidal neurons within a minicolumn are more densely interconnected, have larger EPSPs, and receive common inputs (Peters and Walsh, 1972;Peters and Yilmaz, 1993;Thomson and Deuchars, 1994;Mountcastle, 1997;Tanaka, 1998). Indeed, the definition of cells that are part of a minicolumn is that these cells share common response properties (Mountcastle, 2003).…”
Section: Synaptic Connectivity Between Layer 5 Pyramidal Neurons Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Minicolumns have been proposed to be the basic unit of the neocortex, which are composed of chains of neurons (typically ~80-120 in primates) spanning cortical layers whose cell bodies are vertically aligned within a diameter of ~40-50 μm; about ~50-80 minicolumns link together to form the structural basis of functional columns (Mountcastle, 2003). Another candidate is a related structure referred to as 'bundles', which mainly comprise closely associated apical dendrites of pyramidal cells whose cell bodies are located in different layers (Peters and Kara, 1987;Peters and Sethares, 1996;Peters and Walsh, 1972;Peters et al, 1997). However, both views have met ample criticism (Rockland and Ichinohe, 2004;da Costa and Martin, 2010).…”
Section: The Neocortical Columnmentioning
confidence: 99%